Waste heat recovery technologies and applications. (June 2018) - Jouhara, Hussam; Khordehgah, Navid; Almahmoud, Sulaiman; Delpech, Bertrand; Chauhan, Amisha; Tassou, Savvas A.
Highlights: Waste heat is the energy that is not put into use and is lost into the environment. Recovering waste heat can be conducted through various heat recovery technologies. The functionality of all technologies and their usage is evaluated and described. Heat recovery provides valuable energy sources and reduces energy consumption. Recovery methods in the steel and iron, food, and ceramic industries were reviewed. Abstract: Industrial waste heat is the energy that is generated in industrial processes which is not put into any practical use and is lost, wasted and dumped into the environment. Recovering the waste heat can be conducted through various waste heat recovery technologies to provide valuable energy sources and reduce the overall energy consumption. In this paper, a comprehensive review is made of waste heat recovery methodologies and state of the art technologies used for industrial processes. By considering the heat recovery opportunities for energy optimisation in the steel and iron, food, and ceramic industries, a revision of the current practices and procedures is assessed. The research is conducted on the operation and performance of the commonly used technologies such as recuperators, regenerators, including furnace regenerators and rotary regenerators or heat wheels, passive air preheaters, regenerative and recuperative burners, plate heat exchangers and economisers and units such as waste heat boilers and run around coil (RAC). Techniques are considered such as direct contact condensation recovery, indirect contact condensation recovery, transport membrane condensation and the use of units such as heat pumps, heat recovery steam generators (HRSGs), heat pipe systems, Organic Rankine cycles, including the Kalina cycle, that recover and exchange waste heat with potential energy content. Furthermore, the uses of new emerging technologies for direct heat to power conversion such as thermoelectric, piezoelectric, thermionic, and thermo photo voltaic (TPV) power generation techniques are also explored and reviewed. In this regard, the functionality of all technologies and usage of each technique with respect to their advantages and disadvantages is evaluated and described.